Bacton to Walcott sandscaping, UK: a softer approach to coastal management. Issue 5 (March 2021) - Clipsham, Victoria; Flikweert, Jaap J; Goodliffe, Rob; Courtnell, Edward; Fletcher, Adrian; Hesk, Paul
Abstract : The award-winning Bacton sandscaping scheme in Norfolk, UK, provides an excellent case study of how a coastal management solution can be designed to be more resilient to climate change. It is a large-scale beach nourishment, designed to protect the economically important Bacton gas terminal from cliff and beach erosion. It also reduces flood and erosion risk to the nearby communities of Bacton and Walcott, buying the time they need for adaptation to coastal change. The scheme was inspired by the Dutch zandmotor project, which was successfully translated to a different geography and governance setting.